Pengaruh Kompetensi Pejabat Penatausahaan Keuangan, Sistem Pengendalian Intern, Dan Pengawasan Keuangan Daerah Terhadap Nilai Informasi Pelaporan Keuangan Pemerintah Daerah Kabupaten Indragiri Hulu - Amries Rusli Tanjung; Desi Hariani; Sri Indrastuti (UIR Press, 2016)
This study aimed to examine the effect of the financial administration officials competencies, internal control systems and financial oversight of the local value of the local government financial reporting information to the object of research on education seleruh Indragiri Hulu district, amounting to 41 on education. The sampling technique using purposive sampling. method of data collection is by distributing questionnaires. Analysis using multiple regression. The results of this study it is concluded that the competence of the financial administration officials and financial control area berpengarauh positive significant value of information while the local government financial reporting internal control system variable has no effect on the value of the local government financial reporting information. In this study the magnitude of the effect that the R2 of 0.555 or 55.5% indicate that the competence of the financial administration officials and regional financial oversight of financial reporting information affecting the value of 55.5%, because in the world of government, every part of government must be filled by the right person, ie which has competence in accordance with the qualifications specified. So is the financial oversight of local government has an influence on the financial statements because the information value of the government's financial oversight is a medium that can support to produce reliable financial statements and meets the characteristics of financial reporting information value that has been set. While at 44.5% influenced by other variables.